X-raying the enablers and barriers of e-learning in higher education institutions: a systematic review - Babawande Emmanuel Olawale; Bunmi Isaiah Omodan; Khalid Saddiq (Frontiers in Education)
IntroductionIn recent years, the landscape of higher education has undergone significant transformation, largely driven by technological advancements and the increasing demand for flexible learning options. E-learning, defined as the use of electronic technologies to access educational curricula outside of a traditional classroom, has emerged as a critical component of this evolution. This systematic review aims to identify and analyse the enablers and barriers associated with e-learning in the higher education sector, thereby contributing to the ongoing discourse surrounding its effectiveness and implementation.MethodA comprehensive literature search was conducted across multiple academic databases, including JSTOR, Scopus, ERIC, and Science Direct, to gather relevant studies published between 2015 and 2025. The inclusion criteria focused on empirical research that examined e-learning in higher education. Data were extracted and analysed using thematic analysis to categorise the enablers and barriers identified in the literature.ResultThe review identified several key enablers of e-learning, including technological advancement, diverse learning resources, flexibility and accessibility, and cost-effectiveness. Conversely, barriers such as lack of motivation and self-discipline, technical issues, faculty resistance to change, and inadequate technological infrastructure were also prominent. The findings suggest that addressing these barriers while leveraging enablers is crucial for the successful adoption of e-learning in higher education institutions.ConclusionThis systematic review contributes significantly to the existing body of knowledge surrounding e-learning in higher education. By elucidating the enablers and barriers that influence e-learning implementation, the study provides valuable insights for policymakers, educators, and administrators. As the landscape of higher education continues to evolve, the insights gained from this review can serve as a foundational resource for improving e-learning outcomes and ensuring that institutions are well-equipped to navigate the challenges and opportunities presented by this transformative approach to education. Ultimately, fostering an environment that embraces both the potential of e-learning and the necessary support structures will be crucial for the future success of higher education institutions in an increasingly digital world.